Differential measurement techniques using a programmable Josephson voltage standard - Luna, E. (2024)
This work presents two methods to reconstruct a signal using differential sampling measurements. These measurements were obtained by measuring an AC signal generator against a Programmable Josephson Voltage Standard (PJVS). The main objective of both methods is to eliminate the ubiquitous transients and to reconstruct the signal of the generator under test. In such direction, the Root Mean Square (RMS) value of the digitized signal was obtained and compared using both methods with uncertainties of about 0.9 µV. Therefore, both methods can be applied to measure and characterize an AC generator with a direct traceability to the voltage primary standard reducing the effect of increasing steps and uncertainties in the traceability chain.